The mischief of maxims - Swadling, W (Hart Publishing, 2023)
There is a book to be written on ‘Equitable Legal Method’, if that is not an oxymoron, concerned with how judges wearing their equity hats decide cases. The essential question would be whether, and if so, how, judicial reasoning in equity differs from that at common law. Such a book would have to concern itself with a number of matters. One would be the relationship between law and equity. Another would be the so-called ‘good man’ theory of equity. Others still would be the differences, if any, concerning the criteria for the award of remedies, the use of precedent, the various uses of analogy, the effect of the Judicature Acts 1873–75, and the use of fictions. There would also be a chapter on maxims....